House buyers perception towards smart home concept / Azlina Md. Yassin ... [et al.] - Md. Yassin, Azlina; Masram, Haidaliza; Shafii, Haryati; Yahya, Mohd Yamani; Razali, Mohd Najib (2021)
Smart home concept has been explored for years; however, its proliferation is not yet widespread. Hence, the opportunity has been widely underestimated. This paper aims to identify house buyers' perception towards smart home concept in Malaysia. This research employed quantitative method along the research process, and the results for this paper was collected from 232 respondents which were focusing among groups of house buyers in Klang valley area. The collected data were the analysed. The results show that house buyers were agreed on the smart home concept application in the housing development project. Thus, this research will provide an opportunity for property developers to expand the smart home concept into a new housing development projects in enhancing the quality of life.